2021
DOI: 10.1002/ange.202113448
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Flexibility of the Protein Insertase BamA in the Native Asymmetric Bilayer Elucidated by ESR Spectroscopy

Abstract: The b-barrel assembly machinery(BAM) consisting of the central b-barrel BamA and four other lipoproteins mediates the folding of the majority of the outer membrane proteins.B amA is placed in an asymmetric bilayer and its lateral gate is suggested to be the functional hotspot. Here we used in situ pulsed electron-electron double resonance spectroscopytoc haracterize BamA in the native outer membrane. In the detergent micelles,the data is consistent with mainly an inward-open conformation of BamA. The native me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…Solid-state NMR and single-molecule force spectroscopy techniques are complementary tools for such investigations, in particular for isolated outer membranes (58,59). Using this approach, we showed that BamA displays an increased heterogeneity, in particular at the lateral gate when observed in the native outer membranes (35). Here we extended similar experiments for many other interloop pairs of BamABCDE full complex in intact E. coli cells (see Figs.…”
Section: Conformation Of L3 L6 and The Lateral Gate In E Colisupporting
confidence: 67%
See 3 more Smart Citations
“…Solid-state NMR and single-molecule force spectroscopy techniques are complementary tools for such investigations, in particular for isolated outer membranes (58,59). Using this approach, we showed that BamA displays an increased heterogeneity, in particular at the lateral gate when observed in the native outer membranes (35). Here we extended similar experiments for many other interloop pairs of BamABCDE full complex in intact E. coli cells (see Figs.…”
Section: Conformation Of L3 L6 and The Lateral Gate In E Colisupporting
confidence: 67%
“…Under laboratory environment, BamA and the lipoproteins are expressed at a few thousand (1.5 -6.0 x 10 3 ) copies per cell (62). In our case, overexpression leads to a 100-fold increase in the copy number for BamA (35), which is comparable to the native expression level of some of the OMPs (such as OmpA, OmpC and OmpF). As for membrane protein overexpression in general, the cells may increase the surface area to accommodate the additional copies of BAM molecules (63).…”
Section: Conformation Of L3 L6 and The Lateral Gate In E Colimentioning
confidence: 53%
See 2 more Smart Citations
“…At the same time, cam 8 γCD8+ did not produce any ion current blockages through the truncated CymA similar to native CymA due to their much larger 8-fold symmetric structure (Figure S10). In the future, we will address molecular mechanisms associated with the discrete movement of the N terminus within the pore by targeting specific N terminus mutations using advanced structural methods. Finally, we performed liposome permeation assays to determine the relative permeation rates of neutral cyclic sugars such as αCD and γCD through native and truncated CymA , (Figure c). Under isotonic conditions, αCD diffused through native and truncated CymA pores, whereas γCD did not show any diffusion establishing the importance of molecular size and symmetry for permeation (Figure c).…”
Section: Resultsmentioning
confidence: 99%